Semantic features of sufi terms - Ahmetbekova А. А.; Kuanyshbek А. А. (Journal of Oriental Studies, 2016)
The article deals with Sufi terms. Terms such as “Hauph” (fear), “Raja” (Hope), “Kabd” (compression), “Bast” (extension) were formed on the basis of the Qur’anic text, and it is in some ways defined their concepts. The study found that the Sufi terms are set by the narrowing of the semantic space of word.